2018
DOI: 10.1038/s41388-018-0344-7
|View full text |Cite|
|
Sign up to set email alerts
|

TRIM14 promotes chemoresistance in gliomas by activating Wnt/β-catenin signaling via stabilizing Dvl2

Abstract: Gliomas are a lethal class of brain cancer, with a median survival below 15 months in spite of therapeutic advances. The poor prognosis of this disease is largely attributed to acquired chemotherapy resistance, and new strategies are urgently needed to target resistant glioma cells. Herein, our study demonstrated that tripartite motif-containing 14 (TRIM14) overexpressed in glioma specimens (including tissues and cell lines), and that high level of TRIM14 predicted poor outcome of glioma patients. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…For example, deletionmediated TRIM3 downregulation led to NF-κB constitutive activation through disruption of the NF-κB-IκBα negative feedback loop and promoted lymphatic metastasis of esophageal squamous cell carcinoma cells [20]. Another report demonstrated that TRIM14 stabilized dishevelled (Dvl2) and subsequently activated the canonical Wnt signaling and promoted chemo-resistance in gliomas [21]. Wang and colleges also that the ubiquitin E3 ligase TRIM31 regulates chronic in ammation via NF-κB signal pathway to promote invasion and metastasis in colorectal cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, deletionmediated TRIM3 downregulation led to NF-κB constitutive activation through disruption of the NF-κB-IκBα negative feedback loop and promoted lymphatic metastasis of esophageal squamous cell carcinoma cells [20]. Another report demonstrated that TRIM14 stabilized dishevelled (Dvl2) and subsequently activated the canonical Wnt signaling and promoted chemo-resistance in gliomas [21]. Wang and colleges also that the ubiquitin E3 ligase TRIM31 regulates chronic in ammation via NF-κB signal pathway to promote invasion and metastasis in colorectal cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, tripartite motif-containing 14 (TRIM14) also causes in chemoresistance by TMZ of glioma cells in vitro and in vivo through activating Wnt/β-catenin cascade (Z. Tan et al, 2018). Also, transmembrane glycoprotein nonmetastatic melanoma protein B (GPNMB) may be an inducer for glioma motility and angiogenesis by the activation of Wnt/β-catenin (G. .…”
Section: Oncogenic Effect Of Wnt/ β-Catenin Signaling In Glioma Promentioning
confidence: 99%
“…The Wnt/β‐catenin pathway has been reported to be positively correlated with growth, invasion, and angiogenesis of glioma (He et al, 2018; Wang et al, 2018a). Moreover, chemoresistance and stem cell phenotypes of glioma have been suggested to be associated with the Wnt/β‐catenin signaling by regulating its downstream targets, such as CCND1, c‐MYC, TCF4, LEF1, Oct‐4, and SOX9 (Hsieh et al, 2013; Tan et al, 2018). By detecting the expression of genes involved in maintaining stem cell properties and the β‐catenin activity by measuring the ratio of TOP/FOP luciferase assays (Hsieh et al, 2013), our study showed that miR‐150‐5p inhibited the Wnt/β‐catenin signaling pathway in glioma cells, which was also in agreement with a previous study that exhibited this interaction in non‐small‐cell lung cancer (Dai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%